Substantiation, defense and risk of sensory claims used for packaged foods - Holton, Sarah (Kansas State University, 2019)
Sensory claims, which are descriptive communications about a product’s sensorial attributes, are used in the food and beverage industry to market products every year. Food manufacturers use puffery, non-comparative and comparative (unsurpassed or superiority) sensory claims to communicate to consumers about sensory attributes and how they compare to other brands. However, food manufacturers cannot do so without the proper data to support them. Sensory and consumer perception studies can be used to provide the needed data to support sensory claims in a court of law. However, researchers must ensure data used to support these claims are defendable by a sound research plan which includes representative products tested by a suitable sample size of representative users in key geographical areas. Food companies spend thousands of dollars per year on sensory tests to specifically support food product claims. However, is this research worthy of investment by food companies when the risk, the likelihood of a challenge by competitors, consumers or public interest groups, may be high? Standards for conducting tests to support sensory claims were reviewed. Additionally, challenges of sensory claims were examined to determine the risk by claim type. Parallels from industry standards, sensory and advertising law experts, and cases from the National Advertising Division were drawn to assess the risk associated with different types of food claims and the likelihood of being challenged. Results show that a claim is likely to be challenged if it references or draws comparisons to a competitor’s product. One hundred percent of challenges in the past ten years regarding sensory claims were led by competitors, with a majority resulting in discontinued or modified claims. Therefore, to reduce wasted resources, a food manufacture should spend the time, money and energy to properly conduct claims testing when looking to make comparative claims. Sensory scientists should also review past claims cases and extensively understand how a case is reviewed and what the review panel considers as adequate support. With this knowledge, a sensory scientist can direct which claims to focus their company’s resources on, ensure a robustly designed study, achieve a higher likelihood of succeeding any challenge from the National Advertising Division or a competitor, and thus reduce the overall risk of making a claim. Further research connecting each claim type to actual revenue would be of interest. This information is limited as it lies within each company and may be a moving target as marketplaces and consumer preferences evolve over time.
Keywords: sensory; national advertising division; sensory claims